Inherent fuel consumption and exhaust emission of the cng-petrol bi-fuel engine based at non-loaded operation - Mohsin, Rahmat; Yaacob, Zulkefli; Abdul Majid, Zulkifli; Ashraf, Shameed (Penerbit UTM Press, 2008)
Compressed natural gas (CNG) is the most successful and widely used alternative fuel for vehicles in the market today. Petrol fuelled vehicles are fitted with natural gas vehicle (NGV) conversion kit to enable bi-fuel operation between CNG and petrol. This experimental approach is focused on the fuel consumption, exhaust emission and fuel cost between natural gas and petrol operations. The specially constructed test rig comprises of the bi-fuel fuel system employed in the 1500 cc 12 valves carburettor engine NGV taxis. The inherent fuel consumption and corresponding exhaust emission are acquired at different engine revolution per minute (rpm) during petrol and CNG operation separately. The engine rpm operating without load is varied from idle to more than 5000 rpm to acquire the fuel consumption and exhaust emission profile. These two acquired data are then used to calculate the engine’s air fuel ratio. All three parameters acquired are used to conduct comparisons between petrol and natural gas operation. It is seen that the bi-fuel system operates with air fuel ratio ranging from 19 to 16.3 for petrol operation and ranges from 40 to 18.7 for natural gas operations. The emission during CNG operation clearly shows significant decrease in hydrocarbon (HC), carbon monoxide (CO), carbon dioxide (CO2) and nitrogen oxide (NOx) over the use of petrol. In terms of cost, the use of CNG provides savings exceeding 50% through all engine rpm compared to petrol non-loaded operations.